AN ANALYSIS OF WRITING DIFFICULTIES IN PRODUCING DESCRIPTIVE TEXTS AMONG ENGLISH MAJOR STUDENTS - Laoli, Adieli; Gulo, Arniwati; Anggun Yunita Harita, Epifania; For Enjelina Bate'e, Juni; Niwati Gulo, Lefis (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Writing is a crucial skill in English language learning that requires the integration of linguistic, cognitive, and organizational components, making it one of the most challenging areas for many EFL students. This study aims to analyze the writing difficulties encountered by third-semester English major students in producing descriptive texts and to identify the linguistic aspects contributing to these challenges. Employing a qualitative descriptive research design, data were collected from students’ written descriptive texts and questionnaire responses. Students were asked to compose a descriptive text based on a given topic, while the questionnaire explored their perceptions of writing difficulties. The findings reveal four dominant categories of difficulties: grammatical problems, limited vocabulary, weak text organization, and challenges in developing ideas. Grammar emerged as the most problematic aspect, with frequent errors in tenses, subject–verb agreement, and articles. Vocabulary limitations led to repetitive and inaccurate word choices, while organizational issues appeared in unclear generic structure, weak coherence, and minimal use of cohesive devices. Students also struggled to elaborate ideas, resulting in brief and underdeveloped descriptions. The questionnaire results supported the text analysis, indicating that grammar, vocabulary, idea generation, and organization were perceived as their main challenges. Overall, the study concludes that the writing difficulties experienced by students are influenced by linguistic limitations and insufficient understanding of genre conventions. These findings emphasize the need for integrated and process-oriented writing instruction focusing on grammatical accuracy, vocabulary enrichment, genre awareness, and pre-writing strategies to support students in improving their descriptive writing performance.